The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1007/s003810050343
|View full text |Cite
|
Sign up to set email alerts
|

Application of skull base techniques to pediatric neurosurgery

Abstract: Techniques for skull base surgery have become well established over the last 10 years. Most of these techniques are used in adult patients for skull base tumors and neurovascular diseases. There are very few large series of pediatric patients in whom skull base approaches have been used, because of the rarity of these conditions. The authors would like to present a relatively large series of 26 pediatric patients who underwent skull base approaches for tumor resection. These tumors involved the anterior crania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 12 publications
2
66
0
Order By: Relevance
“…6,8,11,14,17,18,22,26 The largest series reported by Brockmeyer et al 6 included 55 children who underwent skull base approaches for a variety of lesions, including 41 tumors and 2 fibrous dysplasias, in addition to vascular lesions and epidural abscess. The majority of patients did well, with an 11% rate of permanent neurological morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,11,14,17,18,22,26 The largest series reported by Brockmeyer et al 6 included 55 children who underwent skull base approaches for a variety of lesions, including 41 tumors and 2 fibrous dysplasias, in addition to vascular lesions and epidural abscess. The majority of patients did well, with an 11% rate of permanent neurological morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Teo et al 26 reviewed 26 children who underwent skull base approaches for various tumors, including schwannoma, fibrous dysplasia, chordoma, and esthesioneuroblastoma. The rate of immediate postoperative complications was 57% and permanent complications occurred in 30.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior reports, there were few complications noted among patients <21 years of age. 6,7,9 When complications were encountered, they were generally less severe than those reported in older patients. For example, there were no deaths and no CNS complications noted among patients <21 compared with 9 (4.2%) deaths and 14 (6.5%) CNS complications for patients 21 years of age.…”
Section: Discussionmentioning
confidence: 95%
“…In 1999, Teo et al reported a series of 26 pediatric patients who underwent a variety of skull base approaches for the resection of benign and malignant skull base tumors. 6 Five of these patients were treated via anterior craniofacial resection for either esthesioneuroblastoma, 2 fibrous dysplasia, 2 or ossifying fibroma. 1 There were no reported complications, and 80% (4/5) of patients were alive after an average follow-up of nearly 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical anatomy and approaches of cranial basis of adults are well defined in literatures (Brockmeyer et al, 2003;Day et al, 1996;Lang & Samii, 1991;Ribas et al, 2005;Teo et al, 1999). The lesions that effected the cranial basis on children is rare and generally are not treated with major surgery.…”
Section: Introductionmentioning
confidence: 99%